Air‐Sea Turbulent Heat Flux Feedback Over Mesoscale Eddies. Issue 20 (18th October 2021) - Moreton, Sophia; Ferreira, David; Roberts, Malcolm; Hewitt, Helene
Abstract: Air‐sea turbulent heat fluxes play a fundamental role in generating and dampening sea surface temperature (SST) anomalies. To date, the turbulent heat flux feedback (THFF) is well quantified at basin‐wide scales ( ∼ 20 W m − 2 K − 1 ) but remains unknown at the oceanic mesoscale (10–100 km). Here, using an eddy‐tracking algorithm in three configurations of the coupled climate model HadGEM3‐GC3.1, the THFF over mesoscale eddies is estimated. The THFF magnitude is strongly dependent on the ocean‐to‐atmosphere regridding of SST, a common practice in coupled models for calculating air‐sea heat flux. Our best estimate shows that the mesoscale THFF ranges between 35 and 45 W m − 2 K − 1 globally, across different eddy amplitudes. Increasing the ratio of atmosphere‐to‐ocean grid resolution can lead to an underestimation of the THFF, by as much as 80% for a 6:1 resolution ratio. Our results suggest that a large atmosphere‐to‐ocean grid ratio can result in an artificially weak dampening of mesoscale SST anomalies. Plain Language Summary: Sea surface temperature (SST) anomalies are vital for both regulating the Earth's weather and climate, and their generation and attenuation over time are largely determined by turbulent (latent and sensible) air‐sea heat fluxes. Although well‐known at large scales, a quantification of this feedback was not quantified over mesoscale ocean eddies (10‐100 km). This study provides the first global estimate of this feedback, ranging between 35 and 45 W m − 2 K − 1, depending on an eddy's sea surface height anomaly. It is found that coupled climate models underestimate this feedback by up to 80% when the atmosphere grid is configured to a lower spatial resolution than the ocean grid. This massive underestimation suggests that SST anomalies within mesoscale eddies are not reduced enough by air‐sea heat fluxes, and remain too large. Key Points: Turbulent heat flux feedback over coherent mesoscale eddies ranges between 35 and 45 W m − 2 K − 1 Ocean to atmosphere sea surface temperature regridding can underestimate turbulent heat flux feedback by up to 80% in coupled models Coupled models need a coordinated increase in ocean and atmosphere resolutions